The emergence of pottery : technology and innovation in ancient s ocieties - Barnett, William (William K.); Hoopes, John W. (Washington : Smithsonian Institution Press, 1995)
u
Includes bibliographical references and index.
Keywords: Pottery, Prehistoric -- Themes, motives; Pottery, Prehistoric -- Classification; Industries, Prehistoric